The Institutional Mechanisms of Turkey’s "Soft Power" Strategy - Galstyan, Khachik (YSU Journal of International Affairs, 2023)
In modern international relations, the concept of "soft power" plays an important role in the implementation of the state’s foreign policy. Many geopolitical centers of power, such us the United States, EU, Russian Federation, China, have long used "soft power" strategies and its new modification - the concept of "smart power" in their foreign policy arsenal. Recently, the tools of "soft power" have also been successfully implemented by some regional states. Among them, in particular, we can emphasize the Turkey, which has significantly expanded the range of its participation in international and regional political processes. In addition, modern Turkey shows serious ambitions to increase its geopolitical and geo-economic influence in the regions of Central Asia and the South Caucasus. The main purpose of the article is to reveal the features of using the institutional mechanisms of "soft power" strategy in Turkey’s foreign policy arsenal. Within the framework of this study modern conceptual approaches of "soft power", institutional, cultural and economic dimensions of the Turkish "soft power" strategy are discussed. The author argues that after the cultural and economic "expansion" of the countries of the region, Turkey will promote new political agendas, in the service of which the "soft power" strategy will continue to perform their key function.